Epidemiological assessment of the Rift Valley fever outbreak in Kenya and Tanzania in 2006 and 2007 - Jost, Christine; Nzietchueng, S.; Kihu, S.; Bett, Bernard K.; Njogu, G.; Swai, E.S.; Mariner, Jeffrey C. (American Society of Tropical Medicine and Hygiene, 2010)
To capture lessons from the 2007 Rift Valley fever (RVF) outbreak, epidemiological studies were carried out in Kenya and Tanzania. Somali pastoralists proved to be adept at recognizing symptoms of RVF and risk factors such as heavy rainfall and mosquito swarms. Sandik, which means "bloody nose," was used by Somalis to denote disease consistent with RVF. Somalis reported that sandik was previously seen in 1997/98, the period of the last RVF epidemic. Pastoralists communicated valuable epidemiological information for surveillance and early warning systems that was observed before international warnings. The results indicate that an all or none approach to decision making contributed to the delay in response. In the future, a phased approach balancing actions against increasing risk of an outbreak would be more effective. Given the time required to mobilize large vaccine stocks, emergency vaccination did not contribute to the mitigation of explosive outbreaks of RVF.